The labor-supply elasticity and borrowing constraints: Why estimates are biased - David Domeij; Martin Flodén (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
The labor-supply elasticity is a central element in many macroeconomic models. We argue that assumptions underlying previous econometric estimates of the intertemporal labor supply elasticity are inconsistent with incomplete markets economies. In particular, if the econometrician ignores borrowing constraints, the elasticity will be biased downwards. Within our model, the bias may be up to 50 percent. We find a similar bias in PSID data.
Keywords: C20; C50; E20; J22; 330; labor supply elasticity; intertemporal substitution; liquidity constraints; Arbeitsangebot; Substitutionselastizität; Verschuldungsrestriktion; Bias; Theorie